Proteomic analysis of stratum corneum in Cutaneous T‐Cell Lymphomas and psoriasis. Issue 3 (11th February 2019) - Méhul, Bruno; Ménigot, Corinne; Fogel, Paul; Seraidaris, Alexia; Genette, Alexandre; Pascual, Thierry; Duvic, Madeleine; Voegel, Johannes J.
Abstract: Stratum corneum collected by tape stripping from 10 and 24 subjects with cutaneous T‐cell lymphomas (CTCL) or psoriasis, respectively, were compared using quantitative label‐free mass spectrometry analysis. A non‐supervised statistical analysis (Posneg NMF) based on 352 differentially expressed proteins in both CTCL and psoriasis samples was able to separate the two disease groups and finally able to identify a set of 112 proteins that contributed most and significantly to the separation when compared to non‐lesional samples. In addition, Luminex assay revealed that the increase in the amount of chemokines related to the inflammatory response, and immune cell infiltration and recruitment in lesional stratum corneum in CTCL, including CXCL8, CXCL9, CXCL10, CCL27, TNF and sICAM‐1 was in agreement with published data on entire skin biopsies. Proteome analysis using quantitative methods including mass spectrometry and Luminex technology offered the possibility to investigate the relevant protein signature in CTCL and may be helpful to diagnose and investigate the efficacy of treatments in clinical investigations using non‐invasive methods in future.